New Light on the Light of the World - Hughes, Bronwyn Eleanor (Australasian Journal of Victorian Studies, 2019)
William Holman Hunt's Light of the World (1851-53) was a remarkable painting that depicted an idealised vision of his conversion to Evangelical Protestantism.  The derogatory critics and fierce debates that greeted the Pre-Raphaelite paintings at Royal Academy exhibitions from 1850 in no way abated when the Light of the World and other PRB works were hung in 1854.  Acceptance of the Light of the World was gradual, significantly aided by a long explanatory letter from John Ruskin published in The Times (5 May 1854 p. 9) that explained the symbolism in great detail, championing the work as the principal Pre-Raphaelite picture in the Exhbition and one of the noblest works of sacred art ever painted.  Curious Londoners flocked to see it, but there was no inkling then of its influence on religious art, poetry and illustration that would continue well into the twentieth century; no less influential was its impact on stained glass.  Almost immediately it was embraced as a new subject for church windows of all denominations.The global tour of Hunt's larger copy of the Light of the World reached Australia in 1906 where, preceded by clever pre-publicity, it generated huge interest in cities and country centres here and in New Zealand.  The effect of the 'blockbuster' tour was far-reaching, with hundreds of stained glass windows appearing in churches across the country for the next fifty years.  This paper explores William Holman Hunt's co-option of illumination as metaphor and reality, the factors behind the longevity of the Light of the World as a stained glass phenomenon in Australia, and its universal appeal to Protestant church-goers.